Phenomenology Study: Payment Methods on The Marketplace Seen From Islamic Economy Perspective - Dyarini, Dyarini; Mansah, Adi; Alam, Adi; Putri, Aprilia Duwi; Noh, Mohd Shahid Mohd (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This study aims to examine the Islamic view of shopping payment transactions on the marketplace which uses electronic money as well as to examine the Islamic view of special offers on certain products that can be purchased using electronic money. The method used in this research is qualitative research with phenomenological studies. The results showed that the majority of the informants agreed that the electronic money they used did not contain elements of usury although there were informants who had a different opinion. The note that we can highlight here is that the marketplace is not a seller, nor is it a representative of the seller. The marketplace is only a medium that brings sellers and buyers together with certain rules. If it is a debt, it means that the customer must not receive any benefits from GoPay. Thus, if GoPay provides discounts for customers who pay via GoPay, then this includes benefits due to debt. Customers get this benefit, because they give GoPay debt.